Bootstrap ARDL on Health Expenditure, CO2 Emissions, and GDP Growth Relationship for 18 OECD Countries - Wang, Chien-Ming; Hsueh, Hsin-Pei; Li, Fangjhy; Wu, Cheng-Feng (Frontiers in Public Health, 2019)
Using annual time-series data over the period 1975–2017, the researcher applied the bootstrap autoregressive-distributed lag (ARDL) cointegration model developed by McNown et al. (1) to examine whether there is a long run relationship among health expenditure, CO2 emissions, and gross domestic product (GDP) per capita in 18 Organization for Economic Cooperation and Development (OECD) countries. We find cointegration exists in Netherlands when real GDP per capita serves as a dependent variable, in New Zealand when health expenditure is the dependent variable, and in the United States when CO2 emissions are dependent variables. The main results show evidence of a short run relationship between the three variables. The empirical results support that there is a bidirectional causality between health expenditure and GDP growth for Germany and the United States, between CO2 emissions and GDP growth for Canada, Germany, and the United States, and between health expenditure and CO2 emissions for New Zealand and Norway. The results also indicate that there are unidirectional causality in other countries.